2022
DOI: 10.1039/d2cy00577h
|View full text |Cite
|
Sign up to set email alerts
|

Sodium tungsten bronze-supported Pt electrocatalysts for the high-performance hydrogen evolution reaction

Abstract: Based on the strong metal-support interaction, designing and constructing metal-support catalyst is an effective strategy to achieve unique electronic structures and modulate interface microenvironments for improving hydrogen evolution reaction (HER)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…3c), indicating that RuO 2 -DNCTs exhibit faster H 2 generation kinetics in comparison with both RuO 2 -CB and Ru-DNCTs. 40,41 From Fig. S8,† the exchange current density ( j 0 ) of RuO 2 -DNCTs is 8.91 mA cm −2 , larger than that of Pt/C (1.93 mA cm −2 ), Ru-DNCTs (2.04 mA cm −2 ) and RuO 2 -CB (3.31 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 98%
“…3c), indicating that RuO 2 -DNCTs exhibit faster H 2 generation kinetics in comparison with both RuO 2 -CB and Ru-DNCTs. 40,41 From Fig. S8,† the exchange current density ( j 0 ) of RuO 2 -DNCTs is 8.91 mA cm −2 , larger than that of Pt/C (1.93 mA cm −2 ), Ru-DNCTs (2.04 mA cm −2 ) and RuO 2 -CB (3.31 mA cm −2 ).…”
Section: Resultsmentioning
confidence: 98%
“…248–253 Ascertaining that, our group directly fabricated Na x WO 3 nanotube bundle support on a stainless mesh (SM) substrate via a facile hydrothermal method, followed by anchoring Pt nanoparticles with a low load-level (1.44%) on the as-prepared Na x WO 3 nanotube bundles (Pt/R-Na x WO 3 @SM) via the in situ chemical reduction, successfully establishing Pt-sodium tungsten bronze hybrid electrocatalysts. 254 Specially, the Na x WO 3 nanotube bundles were synthesized without using additives and surfactants, and Na 2 S 2 O 8 reagent was employed as an acid source instead of the strong corrosive including HCl, HNO 3 , as well as H 2 SO 4 . As expected, owing to the nanotube bundle morphology with 3D structure and the strong metal–support interaction between Pt and Na x WO 3 , the optimized Pt/R-Na x WO 3 @SM-170 catalyst exhibited excellent HER performance with low overpotentials of 20 and 46 mV at 10 and 100 mA cm −2 , a small Tafel slope of 18.6 mV dec −1 , as well as good stability over 3000 CV runs and CA test for 25 h in 0.5 M H 2 SO 4 media.…”
Section: Design and Fabrication Of Self-supported Electrocatalystsmentioning
confidence: 99%
“…[248][249][250][251][252][253] Ascertaining that, our group directly fabricated Na x WO 3 nanotube bundle support on a stainless mesh (SM) substrate via a facile hydrothermal method, followed by anchoring Pt nanoparticles with a low load-level (1.44%) on the as-prepared Na x WO 3 nanotube bundles (Pt/R-Na x WO 3 @SM) via the in situ chemical reduction, successfully establishing Pt-sodium tungsten bronze hybrid electrocatalysts. 254 Specially, the Na x WO 3 nanotube bundles were synthesized without using additives and surfactants, and Na 2 S 2 O 8 reagent was employed as an acid source instead of the strong corrosive including HCl, HNO 257 The as-synthesized FeOOH@Co 4 N/SSM hybrid electrocatalyst showed a low overpotential of 92 mV at 10 mA cm À2 , a small Tafel slope of 34 mV dec À1 , and excellent stability for the alkaline HER. DFT analyses indicated that the enhanced HER performance of FeOOH@Co 4 N was owing to the suitable e d of Co 4 N adjusted by the strong electronic interaction between Co 4 N and FeOOH.…”
Section: Stainless Steel Substratesmentioning
confidence: 99%
“…The support has the role of dispersing and anchoring the active component, and the interaction force between different supports and the active component varies; thus, the choice of support is equally important. Carbides have been widely studied as typical electrocatalytic supports, 23,24 including carbides such as Mo 2 C, 25–28 WC, 29,30 TiC, 31 and Ni 3 C; 32 they have stronger interactions with metals than carbon, 33 and can provide stronger interaction forces. Among them, boron carbide (B 4 C) is a nonmetallic carbide; it is one of the most stable substances toward acid and has the advantages of a high melting point and good electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%